The influence of cheerleading experiences on career path and development after college in the Philippines - Sta. Maria, Isabella Louise C.; Brebante, Zyra Ruth T. LPT, MSHMS (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2025)
This study explores how collegiate cheerleading influences the development of transferable skills and career trajectories among former student-athletes in the Philippines. While cheerleading is often seen as a terminal sport with limited professional pathways, its potential as a platform for life skills development remains underexplored. The study addresses how cheerleading experiences shape post-graduation career decisions and personal growth. A qualitative exploratory design was employed, using in-depth semi-structured interviews with six former collegiate cheerleaders aged 24–27, all of whom graduated from universities in Metro Manila within the past seven years and are currently employed. Data were analyzed using Braun and Clarke’s six-step thematic analysis approach to identify patterns and meanings within the participants’ narratives. Three key themes emerged: Career Redirection, where participants shifted into new professional paths using skills learned in cheer; Emotional and Identity Transitions, highlighting post-sport adjustment challenges; and Transferable Skills Development, such as time management, leadership, communication, and emotional resilience. The findings suggest that collegiate cheerleading fosters valuable career-relevant competencies and personal development. This underscores the need for institutions to provide structured support for athletes in transition and recognize cheerleading as a credible contributor to workforce readiness. The study calls for greater visibility and institutional validation of non-traditional sports experiences.
Thesis (Bachelor of Sports Science)-University of the Philippines Diliman
Includes bibliographies
Keywords: Cheerleading; Vocational guidance; College athletes